DESAIN DIDAKTIS MATERI LINGKARAN PADA MADRASAH TSANAWIYAH - Arif Abdul Haqq; Durrotun Nasihah; Arif Muchyidin (EduMa: Mathematics education learning and teaching, 2018)
This research is motivated by the learning barriers of epistemology in the matter of circle at Madrasah Tsanawiyah level such as relationship of center angle and circumference, arc length and segment of circle. These learning barriers were found based on data obtained from students in the class who had received the previous circle material then planned to create a proper didactic design. This research aims to develop didactic design on the circle material at Madrasah Tsanawiyah level. This research was conducted in MTs Salafiyah Cirebon City in grade 8 as many as 27 respondents by using descriptive qualitative method. The didactic design was developed through 3 stages, ie didactic situation analysis, metapedadidactic analysis, and retrospective analysis. The result of this research is early didactic design, hypotetic learning trajectory, learning obstacle test result, learning obstacle post-implementation, and didactic empirical design. The early didactic design still needs to be revised to address the LO experienced by the students so that it becomes a more perfect empirical didactic design.